Multilinear projection for face recognition via canonical decomposition - Vasilescu, M Alex O (2011 IEEE International Conference on Automatic Face and Gesture Recognition, 2011)
This paper introduces a new multilinear projection algorithm for appearance-based recognition in a tensor framework. The multilinear projection simultaneously maps an unlabeled image from the pixel space into multiple causal factors underlying image formation, including illumination, imaging, and scene structure. For facial recognition, the most relevant aspect of scene structure is the specific person whose face has been imaged. Our new multilinear projection algorithm, which is based on the canonical decomposition of tensors, is superior to our previously proposed multilinear projection algorithm that is based on an M-mode SVD. To develop our new algorithm, we extend and formalize the definition of the mode-m product, the modem identity tensor, and the mode-m pseudo-inverse tensor. We demonstrate our multilinear projection in the context of facial image recognition and compare its results in simultaneously inferring the identity, view, illumination, etc., coefficient vectors of an unlabeled test image against those obtained using multilinear projection based on the M-mode SVD, as well as against the results obtained using a set of multiple linear projections. Finally, we present a strategy for developing a practical biometric system that can enroll an uncooperative subject using a one or more images and then recognize that subject in unconstrained test images.